Cross-cultural adaptation and psychometric evaluation of the factors influencing adherence to the standard precautions scale – Student version (FIASP-SV) for Saudi Arabian nursing students - Salwa Jadid Alanazi; Jung Yeon (Ellie) Park; Fadiyah Jadid Alanazi; Kyeung Mi Oh (International Journal of Nursing Studies Advances, 2025)
Purpose: To evaluate the psychometric properties and cross-cultural adaptation of the 23-item FIASP-SV, covering four factors—Justification, Leadership, Contextual Cues, and Practice Culture. Background: Nursing students' adherence to Standard Precautions (SPs) is essential for preventing infection transmission and ensuring patient safety. Factors influencing nursing students' adherence to SPs require further investigation through psychometrically validated tools. This study assessed the reliability and validity of the Factors Influencing Adherence to Standard Precautions Scale – Student Version (FIASP-SV), a tool developed in prior research among a sample of Australian students. Methods: The tool was translated into Arabic and adapted for the target population. Using a convenience sample, data were collected from 186 eligible nursing students engaged in patient care across multiple Saudi Arabian universities via an online Qualtrics survey from November 2023 to April 2024. Results: A confirmatory factor analysis (CFA) of the revised four-factor model indicated an acceptable fit (CFI = 0.964, TLI = 0.959, RMSEA = 0.086) and confirmed the scale's internal consistency. Measurement invariance was established between students with and without training, with those who received training demonstrating more leadership skills in adherence to standard precautions. These findings affirm the FIASP-SV as a reliable tool for assessing factors influencing SP practices among Arabic-speaking nursing students. Conclusion: The FIASP-SV is a reliable and valid tool for assessing factors influencing nursing students' adherence to SPs in Saudi Arabia. This tool has significant implications for developing targeted educational interventions to improve SP practices among nursing students in Arabic-speaking contexts.